Epidemiological and Molecular Characterization of Breast Cancer Patients: A Retrospective Study at a Nepalese Tertiary Care Hospital - Rizal, Kushal; Yadav, Birendra Kumar; Rattan, Rajit; Thakur, Alok; Devkota, Mukti; Rai, Ujwal (Medical Journal of Eastern Nepal, 2025)
Background: Breast cancer is a significant health burden in Nepal, ranking among the most common cancers in women, with increasing incidence in younger populations and limited comprehensive data. This study addresses the gap in understanding its clinical and demographic profile in a resource-limited setting. To characterize the demographic, clinical, pathological, and treatment profiles of breast cancer patients at a tertiary cancer hospital in Nepal from 2020 to 2023. Methods: A retrospective analysis was conducted using data from the Health Management Information System for 404 breast cancer patients diagnosed at a tertiary cancer hospital. Patients with non-breast cancer diagnoses (n=2360) were excluded. Data included age, smoking/drinking habits, comorbidities, BMI, tumor laterality, TNM stage, molecular subtypes (ER/PR, HER2 status), and treatment modalities. Univariate analysis described patient characteristics, while bivariate analysis explored associations between age and molecular subtypes. Analysis was performed using STATA. Results: Of 404 patients, 47.5% were aged 45–59 years, 26.5% ≥60 years, and 26% <45 years. Most (52.7%) did not smoke/drink, 33.2% had comorbidities, and 41.6% were overweight/obese. Breast cancer was nearly equally distributed between left (43.3%) and right (44.3%) breasts, with 31.9% at stage III and 10.6% at stage IV. Among 239 patients with immunochemical data, 38.1% were ER/PR+ and HER2-, and 27.6% had triple-negative breast cancer (TNBC), prevalent in the 45–59 age group (59.1%). Treatments included surgery (55.9%, predominantly modified radical mastectomy), chemotherapy (60.6%), radiotherapy (48.0%), hormonal therapy (32.9%), and immunotherapy (5.4%). Hormonal therapy was common in ER/PR+ and HER2- patients. Conclusion: This study highlights a high prevalence of advanced-stage breast cancer and TNBC, particularly in middle-aged women, with a multimodal treatment approach. The findings underscore the need for early detection, comprehensive registries, and targeted therapies to address Nepal’s growing breast cancer burden.